PENGGUNAAN MEDIA FLASHCARD UNTUK MENINGKATKAN PRESTASI BELAJAR BAHASA INGGRIS MATERI THINGS AT HOME BAGI SISWA TUNAGRAHITA DI SLB N PADANG LAWAS UTARA - Hasibuan, Evi Soraya; Kusumastuti, Grahita (Jurnal Penelitian Pendidikan Khusus, 2022)
English lessons for mild mentally retarded children aim to make children have better language skills. The media used, namely flashcards, seeks to improve learning achievement in English and replace the media previously used which are considered less effective. This type of research is classroom action research (CAR), the aim is to find out how to improve learning achievement in English for things at home with flashcard learning media. The research was conducted in collaboration with teachers. Research activities are carried out in several processes, namely planning, observation and reflection. The research was conducted on mentally retarded children in grade IX of SLBN Padang Lawas Utara initials LJ, RW and DIH whose learning achievement in English is still low. The research was carried out in two cycles, each cycle having four meetings. From the results of the study, it was found that the initial abilities of students were LJ 50%, RW 55%, and DIH 50%, then in the first cycle increased to LJ 65%, RW 60%, and DIH 65% In the second cycle, the children's abilities increased, namely LJ 84%, RW 94%, and DIH 87%.